Is there an effect of Bay of Bengal salinity on the northern Indian Ocean climatological rainfall?. (August 2019) - Krishnamohan, K.S.; Vialard, J.; Lengaigne, M.; Masson, S.; Samson, G.; Pous, S.; Neetu, S.; Durand, F.; Shenoi, S.S.C.; Madec, G.
Abstract: The northern Bay of Bengal (BoB) receives a large amount of freshwater directly from monsoonal rains over the ocean, and indirectly through river runoffs. It has been proposed that the resulting strong salinity stratification inhibits vertical mixing of heat, thus contributing to maintain warm sea surface temperature and high climatological rainfall over the BoB. In the present paper, we explore this positive feedback loop by performing sensitivity experiments with a 25-km resolution regional coupled climate model, that captures the main BoB features reasonably well. We confirm that salinity stratification tends to stabilize the upper ocean, thereby increasing the mixed layer warming due to vertical mixing by ∼+0.5 °C.month −1 on annual average. Salinity however also induces a compensating cooling by altering the mixed layer heating rate by air-sea heat fluxes, so that the net effect on climatological surface temperature is negligible. During and shortly after the southwest monsoon, this compensation predominantly occurs through increased cooling by upward latent heat fluxes. During boreal winter, it occurs because salinity favours a thinner mixed layer, which is more efficiently cooled by negative air-sea heat fluxes. These compensations result in a negligible climatological surface temperature and rainfall change at all seasons. This weak influence of salinity stratification on climatological surface temperature and rainfall in our model is robust when applying a flux correction to alleviate model biases, when neglecting the solar absorption below the mixed layer and when using different atmospheric radiation and convective parameterizations.